2017
DOI: 10.9790/3021-0706012229
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Produced Water and Driiling Waste Discharges from the Niger Delta Petroleum Industry

Abstract: Exploratory discharge of produced water and drilling cuttings from oil and gas production has become a major source of pollutant to the biota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Several organic and inorganic components present in produced water can be potentially or more hazardous than the crude oil itself [9]. Organic pollutants can destruct the environment and constitute a health risk to man and the ecosystem [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several organic and inorganic components present in produced water can be potentially or more hazardous than the crude oil itself [9]. Organic pollutants can destruct the environment and constitute a health risk to man and the ecosystem [10].…”
Section: Introductionmentioning
confidence: 99%
“…There was evident change in weight of earthworms during the test across all PFW preparations, and weight can be said to be a more sensitive parameter than survival in accessing pollutant effect in soils ATUANYA, E. I; ISERHIENRHIEN, G. O; EMEJULU, M. J earlier reported by Udochukwu et al (2017). Gazali (2017) reported that the organic and inorganic compounds in produced water have higher toxicity compared to that of crude oil, and the discharge of these toxicity compared to that of crude oil, and the discharge of these toxic constituents and contaminants to the aquatic life and agricultural resources by altering the natural state of the aquatic environment. It is necessary to treat produced water before discharge to avoid the harmful effects that the chemicals in the waste waters may have on the receiving environment.…”
Section: Resultsmentioning
confidence: 99%
“…FW contains a high amount of sodium, and its conductivity is not suitable for irrigation purposes. In addition, the presence of radioactive elements (226 Ra, potassium isotope, 137 Ba, 210 Po, 212 Bi, 214 Bi, 208 Ti, lead isotopes 214 Pb and 210 Pb) in the effluent can degrade the soil and groundwater quality. These observations indicate that FW requires proper treatment before its disposal. FW may be allowed to dispose of (onshore and/or offshore) or reinjected into the abandoned wells only below the ground level (>1000 m) once it complies with the prescribed environmental norms.…”
Section: Introductionmentioning
confidence: 99%